Iron overload associated symptoms and laboratory changes in the Swiss Haemochromatosis Cohort – when a clinician should become attentive (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Hereditary haemochromatosis is a genetic disease characterised by progressive accumulation of iron in organs leading to many unspecific complaints, but even today diagnosis may be delayed. We aimed to identify symptoms associated with iron overload and parameters typical in patients with hereditary haemochromatosis which might help to facilitate detection and diagnosis in daily clinical routine. METHODS We analysed the prospective Swiss Haemochromatosis Cohort (SHC), including 163 patients for whom serum ferritin levels at diagnosis were available. The cohort was stratified according to the degree of iron overload. Substantial iron overload was defined as serum ferritin concentrations ≥1000 µg/ml. RESULTS Patients with substantial iron overload had significantly higher liver enzymes (p